Transmission and diagnosis of equine babesiosis in South Africa - F. T. Potgieter; D. T. de Waal; Elsa S. Posnett (Memorias do Instituto Oswaldo Cruz, 1992)
The transmission and prevalence of Babesia equi and B. caballi are being studied. Rhipicephalus evertsi mimeticus an ixodid tick from Namibia was identified as a new vector of B. equi, however, R. turanicus, previously reported to be a vector, failed to transmit both B. equi and B. caballi in the laboratory. The accurate diagnosis of B. caballi is being investigated because the nature of its low level parasitaemia does not allow easy detection in thin blood smears, routinely used for diagnosis, by clinicians. Consequently its role as a pathogen remains obscure. The importance of identifying infected horses, destined for export to Babesia-free coutries, is also stressed. Thock and thin blood smears, serology (IFAT) and DNA probes are currently employed to study disease prevalence. To date 293 healthy, adult, throughbred horses have been screened by all three methods. The percentage positives are as follows: B. equi 4.4%, 70.6%, 13% and B. caballi 0.7%, 37%, 18.4% respectively. The DNA probes were more sensitive than blood smear examination for diagnosing carrier infections but are probably not sensitive enough to identify all carrier infections. A poor correlation was found between detection of the parasites' DNA and seropositivity. However, polymerase chain reaction could be used to amplify parasite DNA in a particular sample and its could result in more accurate diagnosis.